Sustentabilidade vs Desporto: Como promover a sustentabilidade nos grandes eventos desportivos - Duarte de Almeida, I. (Desporto, educação e cidadania: contextos e aplicações, 2017)
Europe is the continent that has hosted not only the largest number of international sporting events, but also half of all the Olympic Games. Furthermore, it organises the largest number of continent-wide competitions in all sporting disciplines and categories. Due to this fact, there is considerable know-how to exploit and to share among Europeans and with other parts of the world on how to organise major sports events in a sustainable way. Europe could set an example and standards on the organisation and management of sustainable major sporting events, further promoting the economic, social and sporting development in Europe.